Pengembangan formula enteral berbasis ikan lele, tepung ubi jalar putih, dan tepung daun kelor untuk ibu hamil anemia - Sely Tri Anisa; Fitriana Mustikaningrum; Muwakhidah Muwakhidah (Holistik Jurnal Kesehatan, 2026)
Background: Anemia during pregnancy is a health problem that can have serious consequences for the mother and fetus. One way to prevent and treat anemia is through enteral nutrition based on local foods rich in iron and balanced nutrition. Utilizing local foods as enteral nutrition is an alternative to increase nutrient intake, especially iron. Purpose: To develop and evaluate an enteral nutrition formula based on catfish, white sweet potato flour, and moringa leaf flour for pregnant women with anemia. Method: An experimental study using a completely randomized design (CRD) approach was conducted to develop an enteral nutrition formula based on catfish, white sweet potato flour, and moringa leaf flour. The study subjects consisted of three formula groups: F0 = commercial enteral powder (peptisol) as the control formula, and formulas F1 (71%) and F2 (57%). Test parameters included nutritional value, osmolality, flowability, pH, water content, color intensity, and organoleptic testing. The evaluation was conducted by measuring and assessing acceptability by 15 panelists consisting of dietetics students from the Muhammadiyah University of Surakarta. Data were analyzed using the Shapiro-Wilk statistical test, followed by one-way ANOVA if the data were normally distributed, and if there was an effect, followed by the least significant difference (LSD) test. However, if the data were not normally distributed, the non-parametric Kruskal-Wallis statistical test was used, followed by the Dunnett post-hoc test. Results: The statistical test for color intensity (L*) yielded a p-value <0.000, for color intensity (a*) yielded a p-value <0.088, for color intensity (b*) yielded a p-value <0.000, for osmolality yielded a p-value <0.000, for fluidity yielded a p-value <0.000, for acidity yielded a p-value <0.007, and for water content yielded a p-value <0.104. Based on statistical test results, the color category obtained a p-value <0.000, the aroma category obtained a p-value <0.002, the texture category obtained a p-value <0.000, the taste category obtained a p-value <0.003, and all categories obtained p-values ​​<0.001. Formulas F1 and F2 met the energy, protein, fat, carbohydrate, and iron requirements of pregnant women with anemia. F1 had a higher omega-3 and omega-6 content, a faster flow rate, a whitish-green color, a better aroma, and a sweeter taste than F2. F1 was preferred by panelists and had a lower production cost than the commercial formula. Conclusion: Based on cost calculations, enteral formulas based on catfish, moringa leaf flour, and white sweet potato flour are more affordable than commercial enteral formulas. Suggestion: Future research can modify the raw materials or formula manufacturing techniques to meet viscosity standards and reduce osmolality to meet enteral formula standards.   Keywords: Anemia; Catfish; Enteral Nutrition; White Sweet Potato; Moringa Leaf Flour; Pregnant Women.